Disentangling diphtheria: an investigation into its persistence worldwide - Ikejezie, Juniorcaius (2025)
Introduction: Diphtheria is a contagious disease primarily caused by Corynebacterium diphtheriae, which typically affects the respiratory tract and less often the skin. Transmission occurs via exposure to secretions of an infected person. Generally, respiratory diphtheria has a case fatality rate of 5–10%, with higher rates seen among certain groups (e.g., untreated, unvaccinated individuals). After years of decline, diphtheria is experiencing a resurgence, with 24,778 cases reported in 2023 – the highest global case count in over 20 years. The disease has severely affected Haiti, a country that is also facing vulnerability to natural disasters, concurrent health crises, and civil unrest. Despite its impact, diphtheria is still relatively understudied, with questions remaining about the determinants of the observed epidemiological trends and patterns. This PhD thesis aimed to explore drivers of global diphtheria persistence to fill current knowledge gaps.